Three-harmonic optimal multisine input power spectrum for bioimpedance identification. (4th June 2019) - Kwon, H; Rojas, C R; Rutkove, S B; Sanchez, B
Abstract: Objective : The attention towards optimal signals for measuring electrical bioimpedance (EBI) has increased recently due to the many advantages they offer such as, for example, reduced measuring time. Here, the design of a three-harmonic optimized multisine input power spectrum for measuring bioimpedance is considered. Approach : The approach is based on designing the input power spectrum multisine excitation by optimizing a scalar function of the information matrix using the Fricke–Morse model. Main results : Simple analytical equations are provided that can be adopted by the reader to optimize the multisine input power spectrum to satisfy any specific application-related EBI measurement. Significance : The presented signal may be a good choice of excitation signal in EBI applications where optimal excitation power spectrum is desired.